Edward E. Dickerson papers - Dickerson, Edward E., 1831-1914.; Dickerson, Wilton H.
Typewritten transcripts and photocopies of a diary (1863-1864), written as a memoir by Dickerson in 1864 and based on his notes, describing his Civil War service with the 18th and 44th Wisconsin Volunteer Infantry; three letters (1862) from him to his wife, Frances; service record (1861-1864); letters (1909) from Dickerson to his granddaughter describing his life before, during, and after the war; and biographical sketch (1991) of Dickerson by a descendant, Wilton H. Dickerson. Includes material on his campaign experiences in Tennessee and with Gen. William T. Sherman in Georgia where he was captured and later escaped from a Confederate prison camp.
Typewritten transcripts and photocopies.
Union army officer from Wisconsin.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Dickerson, Frances -- Correspondence; Sherman, William T. -- 1820-1891.; United States. -- Army. -- Wisconsin Infantry Regiment, 18th (1861-1865); United States. -- Army. -- Wisconsin Infantry Regiment, 44th (1864-1865); Sherman's March to the Sea; Georgia -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Personal narratives; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Wisconsin -- History -- 19th century; Army officers